2020
DOI: 10.1186/s40529-020-00290-6
|View full text |Cite
|
Sign up to set email alerts
|

Do halophytes and glycophytes differ in their interactions with arbuscular mycorrhizal fungi under salt stress? A meta-analysis

Abstract: Background: Halophytes are better than glycophytes at employing mechanisms to avoid salt injury, but both types of plants can undergo damage due to high soil salinity. Arbuscular mycorrhizal fungi (AMF) can mitigate the damage from salt stress in both halophytes and glycophytes by enhancing salt tolerance and improving energy efficiency. However, variations in mycorrhizal symbiotic efficiency between halophytes and glycophytes were still poorly understood. Therefore, we evaluated the magnitude of AMF effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 80 publications
(132 reference statements)
1
16
0
Order By: Relevance
“…Therefore, choosing the appropriate host plant and AMF species is important for using plant-AMF symbionts to improve salt-affected soil in practical applications. The inoculation of AMF consistently increases shoot K and decreases shoot Na, as demonstrated by several investigators (Augé et al, 2014;Chandrasekaran et al, 2014;Pan et al, 2020) and the outcomes of this meta-analysis. The involvement of CAT, SOD, and POD has been reported in previous meta-analyses (Chandrasekaran et al, 2014;Pan et al, 2020), but we also found that AMF-mediated plant salinity tolerance at low salinity was associated with higher SOD and POD activity, whereas at moderate salinity, more CAT and proline accumulation were also observed in addition to POD and SOD enzymes.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Therefore, choosing the appropriate host plant and AMF species is important for using plant-AMF symbionts to improve salt-affected soil in practical applications. The inoculation of AMF consistently increases shoot K and decreases shoot Na, as demonstrated by several investigators (Augé et al, 2014;Chandrasekaran et al, 2014;Pan et al, 2020) and the outcomes of this meta-analysis. The involvement of CAT, SOD, and POD has been reported in previous meta-analyses (Chandrasekaran et al, 2014;Pan et al, 2020), but we also found that AMF-mediated plant salinity tolerance at low salinity was associated with higher SOD and POD activity, whereas at moderate salinity, more CAT and proline accumulation were also observed in addition to POD and SOD enzymes.…”
Section: Resultssupporting
confidence: 76%
“…In a meta-analysis of 43 studies, Chandrasekaran et al (2014) reported that AMF enhanced plant biomass and uptake of K and reduced uptake of Na and that the fungal species and the host functional groupings were important moderators of that effect. A recent meta-analysis by Pan et al (2020) showed that AMF help halophytes increase the accumulation of inorganic ions (K and Ca) and decrease the accumulation of osmolytes (proline and soluble sugar) to augment biomass production under salinity stress. In contrast, in glycophytes, AMF increase salinity tolerance by their combined influence on increasing soluble sugar, nutrient acquisition, superoxide dismutase, and chlorophyll synthesis and decreasing sodium uptake.…”
Section: Introductionmentioning
confidence: 99%
“…AMF induces different strategies in halophytes to respond to salt environments. Pan et al (2020) expounded that AMF can lead to certain discrepancies in physiological responses to salt stress between glycophytes and halophytes. Moreover, our previous study has shown that AMF induced the DEG that are mainly enriched in carbohydrate and energy metabolism, including the pathways 'carbon fixation in photosynthetic organisms' and 'glyoxylate and dicarboxylate metabolism,' in the halophyte S. salsa at 100 mM NaCl, using transcriptomic analysis (Diao, Dang, Cui, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…AMF can protect from salt stress both in relationship with halophytes and glycophytes [35]. Recently, Pan et al [36] demonstrated on the contrary a greater dependence of glycophytes vs. AMF than of halophytes in the presence of salt stress. Two meta-analyses tried to decipher the benefits of AMF during salt stress [37,38].…”
Section: Arbuscular Mycorrhizal Fungimentioning
confidence: 99%